High fat diet-triggered non-alcoholic fatty liver disease: A review of proposed mechanisms - Lian, Cai-Yu; Zhai, Zhen-Zhen; Li, Zi-Fa; Wang, Lin (Chemico-biological interactions, 2020)
Obesity is characterized by the deposition of excessive body fat, and is caused by energy imbalance, especially when consuming fat-rich diets. High fat diet (HFD)-associated obesity is greatly common in patients with non-alcoholic fatty liver disease (NAFLD) that is emerging as one of the most universal causes of liver disease worldwide, especially in Western countries. In spite of its high prevalence, only a small proportion of affected individuals will become inflamed, followed by fibrosis and chronic liver diseases, and most patients only show simple steatosis. In this case, the full comprehension of the mechanisms underlying the progression of NAFLD is of extreme significance; in spite of progress in this field, awareness on the development of NAFLD is still incomplete. Traditionally, liver steatosis is commonly connected with HFD, obesity, and insulin resistance (IR). Recently, various possible mechanisms have been put forward for liver damage, including endoplasmic reticulum stress, perturbation of autophagy, mitochondrial dysfunction, hepatocellular apoptosis, gut microbiota imbalance, dysregulation of microRNAs, and genetic/epigenetic risk factors, as well as an increase in inflammatory responses, among many others. Collectively, these proposed mechanisms allow for a variety of hits acting together on subjects to mediated NAFLD and will offer a more accurate explanation for progression of NAFLD. Therefore, this review summarizes the present information concerning NAFLD after HFD exposure, as well as discusses possible mechanisms through which it may arise. •High fat diet (HFD) is a crucial contributory factor affecting NAFLD progression.•HFD-triggered possible mechanisms are posited to explain NAFLD pathogenesis.•Currently, effective therapeutic options for NAFLD remain lifestyle interventions.